THE COMMUNITY RELATIONS STRATEGY FOR INCREASING BRAND AWARENESS (A CASE STUDY OF SEVENHUB TRANS7) - Sahara, Raveena Alifia; Hardiyarso, St.; Grafiani, Cecilia Pretty (Universitas Katolik Soegijapranata, 2025)
The increasing competition in digital content has driven the television industry to innovate and adapt to retain its audience. The rapid development of digital platforms forced traditional television media to enhance creativity and establish strong relationships with communities. One such initiative was Sevenhub TRANS7, a platform dedicated to fostering community engagement. This study aim to examine the community relations strategy implemented by Sevenhub TRANS7 to increase brand awareness. This study adopted a qualitative case study approach, using interviews, observations, and documentation as methods of data collection. Based on organization-public relationship (OPR) theory, the findings revealed that Sevenhub applied five dimensions of relationship management, such as trust, openness, engagement, investment, and commitment. As a result, Sevenhub successfully doubled its community members in 2024 compared to 2022.These findings suggested that TRANS7 should establish clear regulations for Sevenhub’s business partner program to facilitate implementation, ensuring mutual benefits for both the company and community members in organizing events.